2008
DOI: 10.1177/1069072708329029
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Neuroticism and Negative Career Thoughts and Feelings to Lack of Information

Abstract: The purpose of this study was to explore correlates of chronic career indecision with multivariate modeling. We examined the effects of neuroticism and negative career thoughts and feelings on lack of information, which is one of the core elements of chronic career indecision. The sample included 310 first-semester students who had entered university study without a declared academic major. The results yielded support for the hypothesized multivariate model. Negative career thoughts and feelings explained a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 29 publications
7
43
0
3
Order By: Relevance
“…It can be said that anger, anxiety, depression, prolonged negative feelings and perceiving ordinary situations as threats, boredom, worries and a tendency towards negative feelings, which are the aspects of neuroticism (Germeijs & Verscheuren, 2011;McCrae & Costa, 2003) are related to experiences such as impetuousness, anxiety, negligence, not thinking in depth, trying to get rid of the decision quickly and giving up the decision, which are the aspects of impetuous indecisiveness. This finding obtained in this study is consistent with the findings of similar studies (e.g., Kelly & Shin, 2009;Lounsbury et al, 2005;Page et al, 2008).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…It can be said that anger, anxiety, depression, prolonged negative feelings and perceiving ordinary situations as threats, boredom, worries and a tendency towards negative feelings, which are the aspects of neuroticism (Germeijs & Verscheuren, 2011;McCrae & Costa, 2003) are related to experiences such as impetuousness, anxiety, negligence, not thinking in depth, trying to get rid of the decision quickly and giving up the decision, which are the aspects of impetuous indecisiveness. This finding obtained in this study is consistent with the findings of similar studies (e.g., Kelly & Shin, 2009;Lounsbury et al, 2005;Page et al, 2008).…”
Section: Resultssupporting
confidence: 94%
“…Moreover, it was found that neuroticism was positively related with impetuous indecisiveness. This is a consistent finding with the findings from the previous studies (e.g., Kelly & Shin, 2009;Lounsbury et al, 2005;Page et al, 2008). Also, this finding shows that neuroticism has a role in impetuous indecisiveness.…”
Section: Resultssupporting
confidence: 93%
“…Kelly and Shin (2009) revealed the association of neuroticism with information deficit, suggesting that individual difference plays a role in the feeling of information deficit. Brown et al's factor analytic work of career indecision (2012) found that information deficit and chronic commitment anxiety were loaded on the same factor.…”
Section: Ambiguity Tolerance In Career Decision Making 16mentioning
confidence: 98%
“…Kelly and Shin (2009) investigated the mediating effects of career pessimism between neuroticism and lack of information, which is considered the main factor in career indecision. They found that the indirect effect of career pessimistic thoughts explained 35% of the variance of lack of information.…”
Section: Career-choice Pessimismmentioning
confidence: 99%